The Impact of Strategic Leadership on the Advancement of SMEs in Rwanda - SIKUBWABO, Theoneste (International Journal of Scientific Research and Management (IJSRM), 2024)
Small and medium-sized enterprises commonly referred to as SMEs are important in the 21st century research since they have stood out as the core players in ensuring economic growth, innovation and job creation in the 21st century's rapidly evolving global economy. The study was carried with the general aim of examining the impact of strategic leadership on the advancement of SMEs in Rwanda. The specific objectives of the study were: to examine the extent to which strategy formulation and planning influences the advancement of SMEs in Rwanda; to establish how strategic communication influences the advancement of SMEs in Rwanda; and to find out the influence of strategy evaluation of the advancement of SMEs in Rwanda. The study adopted a descriptive research design. A total of 500 headers of the SMEs in Kigali Rwanda classified as manufacturing, processing and service SMEs were chosen and a sample size of 150 used with a response rate from the questions used in data collection being 135 translating to 90% return rate. Results indicated that as the per the regression model, it is indicated that 25.8% (R2 =0.568) advancement on SMEs in Rwanda can be explained by a combined effect of the three variables of strategic leadership including strategic formulation/planning, strategic communication and strategic evaluations. This is clear indication of a strong predictive power of the independent variables of the dependent variable SMEs advancement. More narrowly, Strategy Formulation and Planning (B = 0.285, p < 0.001) significantly influenced SME development when controlling for a co-efficient of R2 =.306, suggesting that by optimizing their planning practices an increase in such operations is causally related to greater performance of SME. This factor explained 30.6% of the total variance in SME progression. SME Advancement was likewise influenced signiﬁcantly by Strategic Communication (B = 0.337, p < 0.001) having the highest Beta borrowed value of 0.353 as summarized in Table 9. Better communication practices (defined as clear, consistent messaging and stakeholder engagement) explain 35.3% of the variation in SME growth and development. SME: Strategy Evaluation (B = 0.391, p < 0.001) had the highest effect in SME advancement with Beta value of 0.376 This means that being continually evaluated and corrected according to performance indicators are one of the significant factors in SME success. It was the most powerful predictor of SME advancement, explaining 37.6% of variance in SME advancement. When the hypotheses were tested, the conclusions were made that: H1: There is a significant relationship between strategy formulation and planning and the advancement of SMEs in Rwanda. Result: Accepted (B = 0.285, p < 0.001). Also, as per H2: There is a significant relationship between strategic communication and the advancement of SMEs in Rwanda. Result: Accepted (B = 0.337, p < 0.001). Finally, H3: There is a significant relationship between strategy evaluation and the advancement of SMEs in Rwanda. Result: Accepted (B = 0.391, p < 0.001). Based on these research findings, the study recommends that SMEs in Rwanda should invest in comprehensive strategy formulation processes, implement effective communication systems, continuously evaluate their strategic initiatives, and adopt innovative technologies to enhance their competitiveness and ensure sustainable growth in a rapidly evolving business environment.